Distribution of eight heavy metals in the inner shelf sediments of East China Sea: Risk assessments and sources analysis - Chunjie Wang; Zhangwei Wang; Xiaoshan Zhang (Ecosystem Health and Sustainability, 2021)
Although numerous studies on heavy metals (HMs) in sediments have been carried out in the East China Sea (ECS), the knowledge on the recent pollution levels of HMs in coastal region remains not well understood due to the rapid developments of urbanization in eastern China. In this study, 23 surface samples and 4 core samples are collected in the inner shelf of the ECS. The average dry-weight concentrations follow the descending order of Zn, Cr, Ni, Pb, Cu, As, Cd, and Hg (103.6 ± 26.0, 42.8 ± 12.4, 37.0 ± 9.1, 34.7 ± 11.1, 19.5 ± 10.3, 15.7 ± 11.6, 0.056 ± 0.017, and 0.041 ± 0.017 μg g−1, respectively). HMs concentrations share a similar spatial distribution pattern of TOC content with a decreasing trend from coastline to outer sea. Additionally, HMs concentrations exhibit a decreasing trend from top to bottom sediments, especially for Hg at the open sites due to the wet and dry deposition of atmospheric Hg besides the riverine inputs. The potential ecological risk indices (PERI) values in coastal sediments were about 2–4 times higher than those in open sea. Although the Hg and Cd concentrations were lower by 2–3 orders of magnitude than those of other six metals, the PERI values of Hg (65.5) and Cd (52.1) were 3–40 times higher than those of others. The hierarchical cluster result is consistent with the PCA result, suggesting that Hg, Cd, and As have similar sources and probably mainly originated from anthropogenic emissions.